Awareness of hypertension and depressive symptoms: a cross-sectional study in a primary care population - Rantanen A.; Korkeila J.; Löyttyniemi E.; Saxén U.; Korhonen P. (Taylor and Francis Ltd, 2022)
Objective: To investigate the association of hypertension awareness and depressive symptoms, and to analyse factors predisposing aware hypertensives to depressive symptoms.
Design: Cross-sectional study in a primary care population.
Setting: Cardiovascular risk factor survey in two semi-rural towns in Finland.
Subjects: Two thousand six hundred seventy-six middle-aged risk persons without an established cardiovascular or renal disease or type 2 diabetes.
Main outcome measures: Depressive symptoms, previous and new diagnosis of hypertension.
Results: Hypertension was diagnosed in 47.9% of the subjects, of whom 34.5% (442/1 282) had previously undetected hypertension. Depressive symptoms were reported by 14% of the subjects previously aware of their hypertension, and by 9% of both unaware hypertensives and normotensive subjects. In the logistic regression analysis, both the normotensive (OR 0.62, 95% CI 0.45–0.86) (p = 0.0038) and the unaware hypertensive subjects (OR 0.54, 95% CI 0.35–0.84) (p = 0.0067) had lower risk for depressive symptoms than the previously diagnosed hypertensives. Among these aware hypertensives, female gender (OR 3.61, 95% CI 2.06–6.32), harmful alcohol use (OR 2.55, 95% CI 1.40–4.64) and obesity (OR 2.50, 95% CI 1.01–6.21) predicted depressive symptoms. Non-smoking (OR 0.57, 95% Cl 0.33–0.99) and moderate leisure-time physical activity compared to low (OR 0.53, 95% CI 0.33–0.84) seemed to buffer against depressive symptoms.
Conclusion: Depressive symptoms are common in hypertensive persons even without comorbidities, if the person is already aware of his/her hypertension. Many modifiable, lifestyle associated factors may contribute to the association of hypertension and depressive symptoms.